Developing English Audio-Visual Learning Media to Improve EFL Learners’ Learning Outcomes for Time-Reading Materials - Asmarani, Tabitha Widya; Widagdo, Arif (Journal of Languages and Language Teaching, 2025)
The use of learning media plays a crucial role in enhancing student learning outcomes; however, suboptimal utilization negatively impacts these results. This research aims to develop audio-visual learning media to address this issue. The study employs the Research and Development (R&D) method, utilizing the ADDIE development model, which consists of five phases: analysis, design, development, implementation, and evaluation. Data collection methods include interviews, observations, tests, questionnaires, and documentation. Instruments used in this research comprise interview guides, documentation forms, questionnaires, and pre-test and post-test results. Data analysis is conducted through normality tests, t-tests, and n-gain tests. The t-test result (0.000 < 0.05) indicates a significant difference between pre-test and post-test outcomes. Additionally, the n-gain test yields a score of 76.45, demonstrating the effectiveness of the media before and after implementation. The research subjects consist of fourth-grade EFL learners at elementary schools. Assessments from media experts, material experts, teachers, and students indicate that the developed media is suitable for use in the learning process. The study concludes that audio-visual learning media effectively enhances the learning process and outcomes for EFL elementary school students.